Stem Cell Niche Methods and Protocols - Turksen, Kursad.; Turksen, Kursad. (Methods in Molecular Biology,, 2013)
Interest in a specialized microenvironment or “niche” regulating hemopoietic stem cell function has been steadily growing since the idea was first proposed by Ray Schofield over three decades ago. This growing interest, as well as more recently the interest in cellular-molecular-biochemical characterization of not only the hemopoietic stem cell niche but the niches for other stem cells, incited the compilation of Stem Cell Niche: Methods and Protocols. In this volume, scientists have provided protocols that will provide both a flavor of the field and hopefully stimulate new approaches and methodologies by those interested in the stem cell niche. Written in the successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and notes on troubleshooting and avoiding known pitfalls.   Authoritative and easily accessible, Stem Cell Niche: Methods and Protocols seeks to serve both experts and novices in the stem cell field with well-established protocols on this exciting subject.  .